Do Spanish Medical Students Understand the Concept of Brain Death?. (March 2018) - Ríos, Antonio; López-Navas, A.; López-López, A.; Gómez, F. J.; Iriarte, J.; Herruzo, R.; Blanco, G.; Llorca, F. J.; Asunsolo, A.; Sánchez, P.; Gutiérrez, P. R.; Fernández, A.; et al.
Objective: To analyze the level of understanding of the brain death concept among medical students in universities in Spain. Methods: This cross-sectional sociological, interdisciplinary, and multicenter study was performed on 9598 medical students in Spain. The sample was stratified by geographical area and academic year. A previously validated self-reported measure of brain death knowledge (questionnaire Proyecto Colaborativo Internacional Donante sobre la Donación y Transplante de Organos) was completed anonymously by students. Results: Respondents completed 9275 surveys for a completion rate of 95.7%. Of those, 67% (n = 6190) of the respondents understood the brain death concept. Of the rest, 28% (n = 2652) did not know what it meant, and the remaining 5% (n = 433) believed that it did not mean that the patient was dead. The variables related to a correct understanding of the concept were: (1) being older ( P < .001), (2) studying at a public university ( P < .001), (3) year of medical school ( P < .001), (4) studying at one of the universities in the south of Spain ( P = .003), (5) having discussed donation and transplantation with the family ( P < .001), (6) having spoken to friends about the matter ( P < .001), (7) a partner's favorable attitude toward donation and transplantation ( P < .001), and (8) religious beliefs ( P < .001). Conclusions: Sixty-seven percent of medical students know the concept of brain death, and knowledge improved as they advanced in their degree.